Fatores para near miss neonatal em maternidade de alto risco, Sergipe, Brasil : um estudo caso-controle - Silva, Thais Serafim Leite de Barros (2016)
The neonatal period is almost half of all deaths in children under five years. Neonatal near miss (NMN) is defined as the newborn had a serious complication but survived during the first seven days of life. Although the assessment of NMN identify factors that cause the high number of deaths in the first week of life, few studies have explored this important issue. Objective: To analyze the risk factors for NMN in High Risk Maternity, Sergipe / Brazil. Methods: A case-control study was conducted in which were classified cases of NMN and their respective controls, after evaluation of all records of live births of hospitalized pregnant women for delivery in March-September 2015. After this identification the collection was performed information through interviews with mothers of newborns and verification of records and cards of pregnant women. For data analysis was used descriptive statistics through absolute and relative frequencies, measures of central tendency and variability. Associations were evaluated using the chi-square test and the Student t test, with α = 0.05 significance level. Next was performed logistic regression analysis considering the variables with p <0.20. Multivariate analysis was performed with pre-selected variables in the previous step, according to the hierarchy shown in the conceptual model. The criterion established in this analysis stage to the variables remained in the model was p <0.05. Results: We classified as NMN 125 newborns (cases) and 250 controls selected. It was observed similarity between the average age of the cases (mean = 25.9 + 7) and controls (mean = 25.6 + 6.9). In this study, 97% of mothers interviewed (344/356) attended school. Conducting prenatal care showed protection against the onset of NMN (OR = 0.04; 95% CI: 0,00 to 0.29). The risk of NMN was higher for RNs of pregnant women who had complications during the pregnancy (OR = 13.37; 95% CI: 7.22-24.76). Conclusion: Conducting prenatal care was an important protective factor for NMN.